Lokvikas Milk and Dairy Products: An Online Dairy Product Sales and Management System - Bhandare, Prashant; Jadhav, Omkar; Raut, Indrajit; Godase, Vaibhav; Kulkarni, Vishwanath (International Journal of Computer Sciences and Engineering, 2025)
The Lokvikas Dairy web application project aims to serve as a prototype for an efficient, user-centric, and digitally integrated platform tailored for dairy businesses. The proposed application envisions the digital transformation of traditional dairy operations by offering tools for managing customer interactions, showcasing products, gathering feedback, and ensuring administrative efficiency. This conceptual design reflects the potential of modern web technologies to address challenges in managing customer feedback, product visibility, and real-time data synchronization. While the product is still in development, the outlined methodology and anticipated outcomes emphasize its promise to meet the needs of both end-users and administrators. This project is structured around the core objective of creating a modular, scalable, and user-friendly solution. The envisioned system is designed to bridge the gap between businesses and their customers by offering an interactive digital space for exploring products, submitting reviews, and contacting the business. Firebase Realtime Database has been proposed as the backbone for managing and storing data, ensuring security and efficiency. Through this framework, the project aligns itself with industry standards in creating a reliable digital platform.